Accuracy of Preoperative Templating in Total Hip Arthroplasty. (August 2014) - Riddick, Andrew; Smith, Adam; Thomas, D Phill
Purpose: To assess the accuracy of templating in total hip arthroplasty (THA). Methods: Anteroposterior pelvic radiographs of 20 men and 33 women aged 17 to 80 (mean, 60) years who underwent uncemented THA of the right (n=24) and left (n=29) sides using a single prosthesis were reviewed. A 30-mm–diameter scaling ball was placed between the patient's legs for calculating the magnification factor (MF) of the radiographs. The planned THA was templated using computer software. The positioning of the scaling ball was measured. The preoperative MF was calculated as the size of the ball on radiograph divided by the true size of the ball times 100. The true MF was calculated as the size of the cup on radiograph divided by the true size of the cup times 100. The accuracy of the preoperative MF was calculated as the preoperative MF divided by the true MF times 100. Results: The cup size and stem size were predicted correctly (within one size error) in 87% and 92% of the patients, respectively; no template size was greater than 3 size errors. The overall mean pre-and post-operative MFs differed significantly (122% vs. 127%, p±0.001), as did the mean postoperative MFs between males and females (126% vs. 128%, p=0.006). Assuming the MF was constant, and the postoperative measurement was the most accurate, the mean accuracy of preoperative MF was 96% (range, 89.6–99.9%), whereas the relative mean height of the scaling ball was 30 (range, 1–90) mm away from the correct height. The accuracy of the preoperative MF did not correlate with body mass index, the scaling ball position, and the accuracy of cup and stem templates. Conclusion: If the MF of 127% is constant across different patients, using a MF of 127% is more accurate than using the scaling ball technique.